PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD MELALUI PEMBELAJARAN PAIKEM UNTUK MENINGKATKAN HASIL BELAJAR IPA DAN KECAKAPAN SISWA DI KELAS VI-A SDN 105855 PTPN II TANJUNGMORAWA - Nuraidah Nuraidah (JURNAL TEMATIK, 2014)
Application Type STAD Cooperative Learning Model Learning Through PAIKEM to Enhance Science Learning Outcomes and Student Social Skills Class VIA SDN PTPN II Tanjungmorawa. Postgraduate School of the State University of Medan, 2011. Learning science is dominated by teachers and their regular evaluation form that is more oriented to the results so far provide less opportunity for students to engage actively in the learning process, teachers become the center and learning resources. This is because learning has been more focused on teachers. Model type STAD cooperative learning is one alternative for the learning science, so that expected learning outcomes, social skills and increased student activity. This study is a classroom action research conducted in the classroom VIA SDN 105855 PTPN II Tanjungmorawa by the number of students 31 people. Instruments used to collect test data consists of test results to learn science, observation sheet and observation sheet student activities teacher’s ability to manage learning, and students’ social skills questionnaire. Analysis of the data to see an increase in learning outcomes, social skills and activities of students processed using the program Ms. Excel. From the results of research can be concluded that the application type STAD cooperative learning can enhance students science learning outcomes. It is known that an increased in the average score of the six domains of cognitive science learning outcomes of the cycle I to cycle II, namely: knowledge (C1) increased from 22 to 25; understanding (C2) increased from 19 to 26; application (C3) increased from 21,5 to 22,4; analysis (C4) increased from 19,33 to 22,33; development (C5) increased from 19,33 to 23,33; and proof (C6) increased from 25,5 to 28. Social skills of students has also interested. It can be seen the percentage of total students increasing from the ten indicators are: working in someone else; show social responsibility; controlling emotions; interact with others; manage conflict; tolerace; cultivate sportsmanship and discipline; listening to another friend; communicate with others, and lead. STAD cooperative learning model type should be one alternative for science teachers in presenting lessons